Sequences present in the cytoplasmic domain of CD4 are necessary and sufficient to confer sensitivity to the human immunodeficiency virus type 1 Vpu protein. - Willey, R L (1994)
CD4 is an integral membrane glycoprotein which functions as the human immunodeficiency virus receptor for infection of human host cells. We have recently demonstrated that Vpu, a human immunodeficiency virus type 1-encoded integral membrane phosphoprotein, induces rapid degradation of CD4 in the endoplasmic reticulum. Using an in vitro model system, we demonstrated that Vpu targets specific sequences in the cytoplasmic domain of CD4 to promote its degradation. In this report, we have further delineated regions within CD4 which are required for susceptibility to Vpu. Transfer of the CD4 cytoplasmic region into a heterologous protein, CD8, rendered the chimeric protein sensitive to Vpu-dependent degradation. In contrast, substitution of the CD8 transmembrane domain with the analogous region from CD4 did not confer sensitivity to Vpu. Finally, mutant forms of the CD4 protein containing the extracellular region alone or the extracellular and transmembrane regions linked to a heterologous cytoplasmic domain were not targeted by Vpu. Thus, sequences present in the cytoplasmic domain of CD4 are necessary and sufficient to confer sensitivity to Vpu.